KINERJA KEUANGAN USAHA TAHU UD SUYATMO DI KELURAHAN KLEAK KECAMATAN MALALAYANG KOTA MANADO - Mentari ., Langkay; Elsje Pauline Manginsela; Eyverson ., Ruauw (AGRI-SOSIOEKONOMI, 2018)
The purpose of this study was to determine the financial performance of "UD Suyatmo" Tofu Business in Kleak Village, Malalayang District, Manado. The data used in this study are primary data taken from the business in the form of data in 2016 and 2017. The results show TATO (Total Assets Turn Over) in 2016 of 4.1 times and in 2017 amounting to 4.8 times a year. FATO (Fixed Asset Turn Over) in 2017 is 6.2 times and 2017 is 8.2 times a year. Both are above the industry average which shows that the performance of this business is in good condition. NPM (Net Profit Margin) in 2016 was 61% and 2017 was 46%. NPM is above the industry standard which means that the company's financial performance is in a good category. 2017 ROE (Return On Equity) is 22% and 2016 is 26%. 2016 ROA (Return On Total Assets) was 26% and 2017 amounted to 22%. Both are below industry standards which show the company's financial performance is not good.*eprm*.